2019
DOI: 10.1038/s41427-019-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Organic piezoelectric materials: milestones and potential

Abstract: Research on the piezoelectric response of biomolecules has intensified following demonstration of open circuit voltages of over 20 V in biopiezoelectric generators. Organic piezoelectric nanotubes, fibers, and micro-islands have been grown and studied; however, the lack of fundamental understanding of the piezoelectric effect in nature hinders the rational design of biomaterials to provide a tailor-made piezoelectric response. Advances in high performance computing have facilitated the use of quantum mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 44 publications
1
105
0
Order By: Relevance
“…Other studies indicated the materials-like properties of amino acid assemblies and the piezoelectric properties of amino acid crystals. 353 The overall organization of the metabolites in those systems seems to be related to metabolite amyloids, highlighting once again the similarity between the protein and non-proteinaceous selfassembling systems.…”
Section: Metabolite Amyloidosismentioning
confidence: 94%
“…Other studies indicated the materials-like properties of amino acid assemblies and the piezoelectric properties of amino acid crystals. 353 The overall organization of the metabolites in those systems seems to be related to metabolite amyloids, highlighting once again the similarity between the protein and non-proteinaceous selfassembling systems.…”
Section: Metabolite Amyloidosismentioning
confidence: 94%
“…Glycine (G) is a zwitterionic amino acid and a good model building block for investigating the process of polymorphic crystallization [34][35][36]. At ambient conditions, the crystalline glycines have three distinct structures, α-, ÎČ-, and Îł-structures, where the ÎČand Îł-structures have shear piezoelectricity due to their acentric structures [37][38][39][40]. Herein, the piezoelectricity arises from the displacement of ion in the crystal, as it does in the inorganic materials, and such displacement creates a dipole in local, and a net polarization in bulk, material, as shown in Figure 1c.…”
Section: Piezoelectric Peptidesmentioning
confidence: 99%
“…Energy harvesting from environmental mechanical vibration sources is a promising technology where reliable power sources are unavailable, [ 1,2 ] and it can increase the lifetime of a system while reducing device maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing interest in new energy harvesters to power wearable personal electronic devices without the need for external power sources like batteries. [ 3 ] These devices find potential applications to monitor human gait, [ 2,4,5 ] personalized healthcare, [ 6 ] sports training, [ 7 ] and thus allowing a continuous assessment of health conditions, and are a powerful tool in the development of accurate treatment plans. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation